2010
DOI: 10.1097/wnr.0b013e328337310a
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal horn neurons expressing NK-1 receptors mediate scratching in rats

Abstract: Itch is thought to be signaled by pruritogen-responsive neurons in the superficial spinal dorsal horn. Many neurons here express the substance P NK-1 receptor. We investigated whether neurotoxic destruction of spinal NK-1-expressing neurons affected itch-related scratching behavior. Rats received intracisternal substance P conjugated to saporin (SP-SAP), or saporin (SAP) only (controls), and were subsequently tested for scratching behavior elicited by intradermal 5-hydroxytryptamine. SAP controls exhibited dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 24 publications
5
94
0
1
Order By: Relevance
“…2A), and the mean number of scratch bouts was virtually identical (Fig. lA), such that the mean duration of individual scratch bouts after morphine (2.87 s) was similar to that after naltrexone (2.89 s) and slightly but not significantly different compared to vehicle controls (2.45 s), in agreement with previous reports (8,12,13).…”
Section: Parametric Analysis Of 5-ht-evoked Hindlimb Scratching and Osupporting
confidence: 91%
“…2A), and the mean number of scratch bouts was virtually identical (Fig. lA), such that the mean duration of individual scratch bouts after morphine (2.87 s) was similar to that after naltrexone (2.89 s) and slightly but not significantly different compared to vehicle controls (2.45 s), in agreement with previous reports (8,12,13).…”
Section: Parametric Analysis Of 5-ht-evoked Hindlimb Scratching and Osupporting
confidence: 91%
“…Loss of vesicular glutamate transporter-2 in nociceptors results in reduced pain but enhanced itch, indicating that glutamate release from these nociceptors is dispensable for itch in the absence of pain (41). At the spinal cord level, the peptides GRP and SP, released from TRPV1-expressing nociceptors, activate GRP receptor and NK1 to elicit pruritus (28,31,42). In this study, we further revealed TLR3 as a new player in itch control, to our knowledge, via its peripheral and central actions.…”
Section: Discussionmentioning
confidence: 70%
“…Current evidence indicates that gastrin-releasing peptide (Sun and Chen 2007;Sun et al 2009) and substance P (Carstens et al 2010) may play important roles in the transmission of itch signals from pruriceptors to superficial dorsal horn neurons. Future studies should address possible mechanisms by which primary afferents might be differentially sensitized under pathophysiological conditions associated with chronic itch.…”
Section: Discussionmentioning
confidence: 98%